Economic Valuation of Forest Environmental Services in the form of Water Resources Converted into Electrical Energy with Micro-hydro Power Plants - Bagas Abiyyu Pratama; Jafron Wasiq Hidayat; Yanuar Luqman (Journal of Bioresources and Environmental Sciences, 2026)
Water is an important element in human survival, ironically the benefits of water are often not seen by people who have access to very abundant water. Factor ecology is a determinant of water availability in an area, as is the case in the village of Geneng, Bulukerto, Wonogiri, Central Java. The preservation of the forest, which was initiated by a figure named Mbah Sadiman around the village, who planted Ficus Benjamina, is allegedly a factor in the availability of water in the village is very abundant compared to a few decades ago after forest fires that cause water shortages during the dry season. Forest spring water sources are able to produce an average discharge of 71.78 liters/s. The discharge can generate electrical energy with a Micro-hydro Power Plant of 4.5668 kW, which can generate a cash flow of IDR 57.7 million/year. The Net Present Value (NPV) obtained is IDR 224 million with a project life of 20 years. The economic value generated by forest environmental services in the form of water resources has significant economic value, and this value is obtained only from the use of electrical energy.